Transaction Costs, Information Technology and Development - Nirvikar Singh (University of California, Economics Department, 2004)
This paper explores potential channels through which information technology (IT) affects economic development. The channel emphasized here is the reduction of transaction costs through the use of information technology. We discuss the nature of transaction costs, their possible impacts on economic outcomes, and the impacts of IT on transaction costs. We provide a theoretical discussion of how a reduction in transaction costs may affect the number of intermediate goods that are produced, and in turn how that number may affect the development path of the economy. We then draw on our fieldwork in rural India that examined the economics of rural Internet kiosks, and relate this multifaceted case study to the theoretical discussion of transaction costs. We conclude with a broader discussion of the potential impact of IT on developing economies.
Keywords: 330; transaction costs; information technology; Internet; development; India